2017
DOI: 10.1111/sode.12258
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and implications of social withdrawal in early childhood: A first look at social avoidance

Abstract: The goals of the present research were to: (a) develop and provide preliminary validation of a parent-rated measure of social avoidance in early childhood; and (b) to evaluate a conceptual model of the direct and indirect links among young children's social withdrawal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
148
4
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(164 citation statements)
references
References 50 publications
(116 reference statements)
9
148
4
3
Order By: Relevance
“…For instance, research in North America found that shy preschoolers frequently opt to play alone in the presence of peers and, consequently, may be more excluded by peers (Coplan, Ooi, Rose‐Krasnor, & Nocita, ; Ooi, Baldwin, Coplan, & Rose‐Krasnor, ). Shy preschoolers also tend to display more internalizing problems, such as anxious‐withdrawn behaviors and depressive symptoms (Coplan, Ooi, Xiao, & Rose‐Krasnor, ; Kopala‐Sibley & Klein, ; Sette, Zava, Baumgartner, Baiocco, & Coplan, ). Furthermore, shyness (behavioral inhibition) is a risk factor for later social anxiety disorder (Clauss & Blackford, ), and stable, increasing levels of shyness in a longitudinal study of Norwegian children were found to predict symptoms of anxiety and depression in adolescence (Karevold, Ystrøm, Coplan, Sanson, & Mathiesen, ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, research in North America found that shy preschoolers frequently opt to play alone in the presence of peers and, consequently, may be more excluded by peers (Coplan, Ooi, Rose‐Krasnor, & Nocita, ; Ooi, Baldwin, Coplan, & Rose‐Krasnor, ). Shy preschoolers also tend to display more internalizing problems, such as anxious‐withdrawn behaviors and depressive symptoms (Coplan, Ooi, Xiao, & Rose‐Krasnor, ; Kopala‐Sibley & Klein, ; Sette, Zava, Baumgartner, Baiocco, & Coplan, ). Furthermore, shyness (behavioral inhibition) is a risk factor for later social anxiety disorder (Clauss & Blackford, ), and stable, increasing levels of shyness in a longitudinal study of Norwegian children were found to predict symptoms of anxiety and depression in adolescence (Karevold, Ystrøm, Coplan, Sanson, & Mathiesen, ).…”
Section: Introductionmentioning
confidence: 99%
“…Findings from more recent work suggest that there may indeed be a number of reasons why individuals withdraw from the peer group (Coplan, Ooi, & Nocita, 2015). Importantly, withdrawal characterized by different social motivational substrates appear to be differentially associated with socio-emotional adjustment Coplan, Ooi, Xiao, & Rose-Krasnor, 2018;Nelson, 2013). For example, whereas unsociability (i.e., a non-fearful preference for solitude) appears to be a relatively benign form of withdrawal, shyness is associated with socio-emotional maladjustment, including heightened feelings of social anxiety.…”
Section: List Ofmentioning
confidence: 99%
“…For example, whereas unsociability (i.e., a non-fearful preference for solitude) appears to be a relatively benign form of withdrawal, shyness is associated with socio-emotional maladjustment, including heightened feelings of social anxiety. Social avoidance appears to be associated with the most pervasive socio-emotional difficulties, and may be uniquely linked to symptoms of depression (Coplan & Armer, 2007;Coplan, Ooi, Xiao, et al, 2018;. As such, it is important to identify the possible mechanisms through which subtypes of socially withdrawn youth may (or may not) develop internalizing problems.…”
Section: List Ofmentioning
confidence: 99%
See 2 more Smart Citations